Alcohol consumtion habits among young adults, with sedentary and active live style - Gligorovski A.,&; Shukova Stojmanovska D. (Faculty of physical education, sport and health, 2018)
Physical activities, as part of good life habits, are associated with lower alcohol intake, and therefore people who exercise regularly are assumed to consume less alcohol. The aim of this research was to determine the level of alcohol consumption among young respondents, aged 13-30 years, in relation to sex and physical activity. This investigation was conducted on 68 respondents divided in two groups regarding the gender, and these groups were divided into two additional subgroups in terms of level of physical activity: active and sedentary individuals. The information about alcohol consumption habits were obtained through a questionnaire. Our results on the habits of young people on alcohol consumption show that the percentage of male respondents as alcohol consumers is slightly but insignificantly larger than in female. On the questions related to the frequency of drinking, a significantly bigger number of male respondents drink 1-2 a week, while the female respondents drink 1-2 monthly. A significant number of female respondents tasted alcohol for the first time two years after the male respondents, which is between the ages of 14-16. Male respondents started consuming alcohol earlier than female respondents. Men drink more often than women. Women with a sedentary lifestyle started consuming alcohol earlier in their life, and drink more often than women who have an active lifestyle. Men with active and sedentary lifestyles have similar alcohol consuming habits considering the frequency and the amount. The main difference in alcohol consumption in men was that those with sedentary lifestyle started consuming alcohol earlier in their life.
Keywords: alcohol, consumption, physical activity, sedentary